Effects of a new thyrotropic drug isolated from Potentilla alba on the male reproductive system of rats and offspring development - Lubov V. Krepkova; Valentina V. Bortnikova; Aleksandra N. Babenko; Praskovya G. Mizina; Vladimir A. Mkhitarov; Kathleen M. Job; Catherine M. Sherwin; Elena Y. Enioutina (BMC, 2021)
Abstract Background The dysfunction of the thyroid gland is a common medical condition. Nowadays, patients frequently use medicinal herbs as complementary or alternative options to conventional drug treatments. These patients may benefit from treatment of thyroid dysfunctions with Potentilla alba L. preparations. While it has been reported that Potentilla alba preparations have low toxicity, nothing is known about their ability to affect reproductive functions in patients of childbearing age. Methods Male Wistar rats were orally treated with a thyrotrophic botanical drug, standardized Potentilla alba Dry Extract (PADE), at doses 8 and 40 times higher than the median therapeutic dose recommended for the clinical trials, for 60 consecutive days. Male Wistar rats receiving water (H2O) were used as controls. After completing treatment, half of the PADE-treated and control males were used to determine PADE gonadotoxicity, and the remaining half of PADE-treated and control males were mated with intact females. Two female rats were housed with one male for two estrus cycles. PADE effects on fertility and fetal/offspring development were evaluated. Results Herein, we report that oral treatment of male Wistar rats with PADE before mating with intact females instigated marked effects on male reproductive organs. Treatment significantly decreased the motility of the sperm and increased the number of pathological forms of spermatozoa. Additionally, a dose-dependent effect on Leydig cells was observed. However, these PADE effects did not significantly affect male fertility nor fetal and offspring development when PADE-treated males were mated with intact females. Conclusions PADE treatment of male rates negatively affected sperm and testicular Leydig cell morphology. However, these changes did not affect male fertility and offspring development. It is currently not known whether PADE treatment may affect human male fertility and offspring development. Therefore, these results from an animal study need to be confirmed in humans. Results from this animal study can be used to model the exposure-response relationship and adverse outcomes in humans.